Incorporating Urban Drainage System Resilience in Public Policies for a City in a Developing Country—Colombia - Galarza-Molina, Sandra; Torres-Lozada, Patricia; Galvis-Castaño, Alberto (Frontiers in Water, 2022)
Scientific studies have shown that conventional practices on urban drainage management are not sustainable. Resilience has emerged to manage and protect socio-ecological and socio-technical systems. This paper reviews how urban drainage system resilience has been incorporated effectively into public policies worldwide to make recommendations for a city in a developing country. To this end, we carried out literature reviews to identify key actions that other countries have implemented and determine the policy baseline at the national level for Colombia. These findings were used to formulate recommendations for incorporating resilience in national Public Policies, which were validated during a workshop with experts. At the national level, we evidenced pathways to update public policies, involving a multi-step local and national activities process. A pilot project using the Santiago de Cali Resilience Strategy was proposed to implement the initial findings and identify actions by the stakeholder group. The process can be monitored and improved to be replicated in other areas.